Smartphone-Based Answering to School Subject Questions Alters Gait in Young Digital Natives - Caramia, Carlotta; D'Anna, Carmen; Ranaldi, Simone; Schmid, Maurizio; Conforto, Silvia (Frontiers in Public Health, 2020)
Smartphone texting while walking is a very common activity among people of different ages, with the so-called digital natives being the most used to interacting with an electronic device during daily activities, mostly for texting purposes. Previous studies have shown how the concurrency of a smartphone-related task and gait can result in a worsening of stability and to an increased risk of injuries for adults; an investigation of whether this effect can be identified also in people of a younger age can improve our understanding of the risks associated with this common activity. In this study, we recruited 29 young adolescents (12 ± 1 years) to test whether walking with a smartphone increases fall and injuries risks, and to quantify this effect. To do so, participants were asked to walk along a walkway, with and without the concurrent writing task on a smartphone; several different parameters linked to stability and risk of fall measures were then calculated from an inertial measurement unit and compared between conditions. Smartphone use determined a reduction of spatio-temporal parameters, including step length (from 0.64 ± 0.08 m to 0.55 ± 0.06 m) and gait speed (1.23 ± 0.16 m/s to 0.90 ± 0.16 m/s), and a general worsening of selected indicators of gait stability. This was found mostly independent from experience or frequency of use, suggesting that the presence of smartphone activities while walking may determine an increased risk of injury or falls also for a population that grew up being used to this concurrency.